Promoting Shared Prosperity: The Relevance Of Social Cohesion In Developed And Developing Countries - Noer Hazila Ismail (Asia-Pacific Journal on Religion and Society, 2019)
In April 2013, the issue of greater inequalities and social exclusion reckoned to be the result of economic growth led the World Bank to set the new goal, to end extreme poverty and promote shared prosperity. Interestingly, the approach of the contemporary solution is largely in consonance with the maqasid or objectives of the Shari’ah. Islam is a universal religion and addresses the entire mankind, not the believers alone. It is, therefore, no surprise that people irrespective of faith do often think along the Islamic lines. The notion of social cohesion is often used with different meanings, however its constituent elements remain the same which includes social inclusion, social capital and social mobility. This study analyzed the impact of the social cohesion, by adopting a cross-country approach. Specifically, the study examined the impact of social cohesion to the poorest quintiles of the population by evaluating the relationship between the factors and the changes in the per capita income of the poor of the developed and developing countries. Panel regression was applied to examine the significance of the social cohesion towards the shared prosperity of the developed and developing countries. It is hoped that this study will serve as an effective mechanism for poverty eradication in the respective countries.